Gastrointestinal Stability and Cytotoxicity of Bacteriocins From Gram-Positive and Gram-Negative Bacteria: A Comparative in vitro Study - Soltani, Samira; Zirah, Séverine; Rebuffat, Sylvie; Couture, Frédéric; Boutin, Yvan; Biron, Eric; Subirade, Muriel; Fliss, Ismail (Frontiers in Microbiology, 2022)
Bacteriocins are receiving increased attention as potent candidates in food preservation and medicine. Although the inhibitory activity of bacteriocins has been studied widely, little is known about their gastrointestinal stability and toxicity toward normal human cell lines. The aim of this study was to evaluate the gastrointestinal stability and activity of microcin J25, pediocin PA-1, bactofencin A and nisin using in vitro models. In addition cytotoxicity and hemolytic activity of these bacteriocins were investigated on human epithelial colorectal adenocarcinoma cells (Caco-2) and rat erythrocytes, respectively. Pediocin PA-1, bactofencin A, and nisin were observed to lose their stability while passing through the gastrointestinal tract, while microcin J25 is only partially degraded. Besides, selected bacteriocins were not toxic to Caco-2 cells, and integrity of cell membrane was observed to remain unaffected in presence of these bacteriocins at concentrations up to 400 g/mL. In hemolysis study, pediocin PA-1, bactofencin A, and nisin were observed to lyse rat erythrocytes at concentrations higher than 50 g/mL, while microcin J25 showed no effect on these cells. According to data indicating gastrointestinal degradation and the absence of toxicity of pediocin PA-1, bactofencin A, and microcin J25 they could potentially be used in food or clinical applications.